2019
DOI: 10.1158/1078-0432.ccr-18-1443
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Homologous Recombination Deficiency in High-grade Endometrial Carcinomas

Abstract: Purpose: The elevated levels of somatic copy-number alterations (SCNAs) in a subset of high-risk endometrial cancers are suggestive of defects in pathways governing genome integrity. We sought to assess the prevalence of homologous recombination deficiency (HRD) in endometrial cancers and its association with histopathologic and molecular characteristics.Experimental Design: Fresh tumor tissue was prospectively collected from 36 endometrial cancers, and functional HRD was examined by the ability of replicating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 53 publications
1
118
2
Order By: Relevance
“…e P value was calculated over negative nuclear WT-1 expression or positive nuclear WT-1 expression (encompassing both heterogeneous and diffuse positive staining). BRCA1/2-mediated HR is commonly abrogated in TP53-mutated serous-like ECs (24). Cells that are HRD are more prone to DNA damage due to the error-prone repair of the DNA double-strand breaks caused by ROS and estrogen metabolites (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e P value was calculated over negative nuclear WT-1 expression or positive nuclear WT-1 expression (encompassing both heterogeneous and diffuse positive staining). BRCA1/2-mediated HR is commonly abrogated in TP53-mutated serous-like ECs (24). Cells that are HRD are more prone to DNA damage due to the error-prone repair of the DNA double-strand breaks caused by ROS and estrogen metabolites (58).…”
Section: Discussionmentioning
confidence: 99%
“…The "serous-like/SCNA-high" molecular subclass has poorest clinical outcome and interestingly displays molecular similarities to both basal-like breast cancer and HGSOC, including a high number of SCNAs and frequent TP53 mutations. Moreover, recent studies demonstrated that serouslike/SCNA-high ECs also frequently are HRD (22)(23)(24). This raises the question whether ECs occurring in gBRCA1/2 carriers might be enriched for certain features, but studies comprehensively evaluating this have not been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination repair capacity has been successfully used as a marker to identify patients that benefit from poly (ADP ribose) polymerase inhibitors (PARPi) in high‐grade serous ovarian cancer (HGSOC) . HGSOC and serous EC have very similar molecular genetic alterations; recent data show that a subset of p53mut EC are homologous recombination‐deficient, and some of these EC can arise in the context of germline BRCA1/2 mutations . The exact prevalence of HRD in p53mut EC is currently unknown; in a small and selected set of cases it was 46% .…”
Section: Potential Role For Molecular Characteristics In the Treatmenmentioning
confidence: 99%
“…66,67 HGSOC and serous EC have very similar molecular genetic alterations 4 ; recent data show that a subset of p53mut EC are homologous recombination-deficient, and some of these EC can arise in the context of germline BRCA1/2 mutations. [68][69][70][71] The exact prevalence of HRD in p53mut EC is currently unknown; in a small and selected set of cases it was 46%. 68 Together, these data build upon a rationale to target homologous recombination in p53mut EC, particularly those that are HRD.…”
Section: R O L E O F H R D I N E C T R E a T M E N Tmentioning
confidence: 99%
See 1 more Smart Citation